PREDIKSI DAN ANALISIS KESTABILAN GERAK LONGITUDINAL KAPAL BERSAYAP WING-IN-SURFACE EFFECT - Muhammad, Hari (Mesin, 2004)
This paper discusses the stability of Wing-in-Surface-Effect (WiSE) craft. The aerodynamic parameters of new WiSE craft jointly designed by the Agency for the Assessment and Application of Technology, Indonesian Aerospace Ltd. and Institute of Technology Bandung are estimated using software Digital Datcom of the US Air Force. The aerodynamic parameters are used to predict the longitudinal stability characteristics of the WiSE craft. The surface effect on some aerodynamic parametes that influence the longitudinal stability of the WiSE craft will be discussed in this paper.